Neuronal function of Tbx20 conserved from nematodes to vertebrates. - Pocock, R; Mione, M; Hussain, S; Maxwell, S; Pontecorvi, M; Aslam, S; Gerrelli, D; Sowden, J; Woollard, A (2008)
The Tbx20 orthologue, mab-9, is required for development of the Caenorhabditis elegans hindgut, whereas several vertebrate Tbx20 genes promote heart development. Here we show that Tbx20 orthologues also have a role in motor neuron development that is conserved between invertebrates and vertebrates. mab-9 mutants exhibit guidance defects in dorsally projecting axons from motor neurons located in the ventral nerve cord. Danio rerio (Zebrafish) tbx20 morphants show defects in the migration patterns of motor neuron soma of the facial and trigeminal motor neuron groups. Human TBX20 is expressed in motor neurons in the developing hindbrain of human embryos and we show that human TBX20 can substitute for zebrafish tbx20 in promoting cranial motor neuron migration. mab-9 is also partially able to rescue the zebrafish migration defect, whereas other vertebrate T-box genes cannot. Conversely we show that the human TBX20 T-box domain can rescue motor neuron defects in C. elegans. These data suggest the functional equivalence of Tbx20 orthologues in regulating the development of specific motor neuron groups. We also demonstrate the functional equivalence of human and C. elegans Tbx20 T-box domains for regulating male tail development in the nematode even though these genes play highly diverged roles in organogenesis.